The preferences of consumers for organic tea: Evidence from a stated choice experiment - Hashem Mahmoudi; Mostafa Farajpour; Samira Afrasiabi (Journal of the Saudi Society of Agricultural Sciences)
Organic farming plays an important role in sustainable development. Advances in organic farming can be based on consumer preferences and, therefore, it is important to determine how consumers prefer organic products in moving towards sustainable agricultural development. Choice experiment (CE) is a stated-preference approach to evaluate consumer preferences. Some respondents may not take into account all attributes in the process of CE, thereby causing heterogeneity in collective respondent behavior. The present study uses the “Endogenous Attendance Attributes (EAA)” model which considers heterogeneity in consumer behavior towards selecting organic tea. The analysis was performed according to the preferences of several participants who were selected randomly among consumers of organic tea. The conditional logit and EAA models generated results, along with the calculated coefficients of the attributes of organic tea. Ultimately, these values appeared compatible with consumer preferences for organic tea. Consumers varied in their willingness to pay for organic tea, as revealed by the two models.